OTHR-07. Systematic Review and Meta-analysis of Lung Cancer Brain Metastasis and Primary Tumor PD-L1 Expression Discordance. (9th August 2021) - Tonse, Raees; Rubens, Muni; Appel, Haley; Tom, Martin C; Hall, Matthew D; Odia, Yazmin; Mehta, Minesh P; McDermott, Michael W; Ahluwalia, Manmeet S; Kotecha, Rupesh
Abstract: Background: Novel immunotherapeutic strategies, such as those targeting the PD-1/PD-L1 axis, are promising in patients with metastatic lung cancer and are often administered when tumors show PD-L1 positivity. The objective of this study was to analyze PD-L1 receptor discordance in tumor cell between the primary tumor and lung cancer brain metastasis (LCBM). Methods: A systematic review of series published prior to April 2021 obtained from the Medline database of biopsied or resected LCBM evaluating PD-L1 discordance was performed using PRISMA guidelines. Weighted random effects models were used to calculate pooled estimates. Results: Six full-text articles (n=247 patients) with a median of 32 patients in each study (range: 24–73 patients) reported PD-L1 receptor expression analyses of both primary lung tumors and brain metastases. The majority of patients (81%) were smokers, with 67% non-small cell lung cancer and 33% small cell lung cancer. The pooled estimate for overall PD-LI receptor concordance between primary and LCBM was 76% (95% CI: 52%-90). The positivity rate varied when analyzed by various cutoff levels of PD-L1 expression; for <1% expression, it was 41% (95% CI: 22%-62%) for primary vs. 58% (95% CI: 35%-78%) for LCBM; for PD-L1 expression of 1–50%, it was 24% (95% CI: 13%-40%) vs. 19% (95% CI: 10%-33%); and for PD-L1 >50% it was 12% (95% CI: 4%-33%) vs. 21% (95% CI: 14%-29%) ( p =0.425). The pooled estimate for overall PD-LI receptor discordance between primary and LCBM was 17% (95% CI: 10%-27%). Meta-regression analysis showed that age, sex, smoking status, and histology were not associated with PD-LI receptor discordance. Conclusions: PD-L1 status discordance in tumor cell occurs in approximately 20% of LCBM, with the greatest discordance in the <1% expression category. Awareness of this discordance is important for the selection of immune checkpoint inhibitor therapy as well as in the analysis of patterns of failures.